Comparison Analysis of Real Costs with Ina-CBG Rate's Ischemic Stroke Disease in Installations in Regional Public Hospitals X in Banda Aceh 2019 - Mulyanti Mulyanti; Irwan Saputra; Maimun Syukri; Nurjannah Nurjannah; Nova Dian Lestari (Budapest International Research and Critics University, 2020)
The government health financing system paid for hospital using the INA-CBG’s method. Stroke is the third most common cause of death after heart disease and cancer and stroke rank first as a cause of disability. Thus, the treatment of strokes due to disability and recurrent strokes requires a fairly high maintenance cost. Results: The total cost of ischemic stroke in 345 hospitalized cases with a total real cost was IDR 2.800.210.362 and a total cost of INA-CBG's of IDR 2.830.254.600.This has a significant difference, as well as severity levels and comorbidities. There is a difference between the real hospital rates and INA-CBG’s rates with a value of P = 0,000. The cost of caring for ischemic stroke patients the most cost was accommodation (22%). Conclusion: There is a difference between the real hospital costs and the INA-CBG’s rates for ischemic stroke patients at X Hospital, this is because there is still a negative difference associated with severity level, type of comorbid, length of stay and class of care.